2022
DOI: 10.1186/s13046-022-02422-1
|View full text |Cite
|
Sign up to set email alerts
|

POLE/POLD1 mutation and tumor immunotherapy

Abstract: POLE and POLD1 encode the catalytic and proofreading subunits of DNA polymerase ε and polymerase δ, and play important roles in DNA replication and proofreading. POLE/POLD1 exonuclease domain mutations lead to loss of proofreading function, which causes the accumulation of mutant genes in cells. POLE/POLD1 mutations are not only closely related to tumor formation, but are also a potential molecular marker for predicting the efficacy of immunotherapy in pan-carcinomatous species. The association of POLE/POLD1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 70 publications
2
39
0
1
Order By: Relevance
“…Te SBS10a, only present in the highrisk group, may be generated by POLE exonuclease domain mutations. Te exonuclease domain of POLE recognizes and removes wrong bases generated during replication [92]. Te mutations in the exonuclease of POLE, referred to as hypermutators, cause a 10-to-100fold increase in the mutation rate during replication [92], which is in accordance with the interesting fnding that CC patients with several hypermutators had the most kataegis in the high-risk group.…”
Section: Discussionsupporting
confidence: 58%
“…Te SBS10a, only present in the highrisk group, may be generated by POLE exonuclease domain mutations. Te exonuclease domain of POLE recognizes and removes wrong bases generated during replication [92]. Te mutations in the exonuclease of POLE, referred to as hypermutators, cause a 10-to-100fold increase in the mutation rate during replication [92], which is in accordance with the interesting fnding that CC patients with several hypermutators had the most kataegis in the high-risk group.…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, some studies also reported that the responsiveness or tolerance to immunotherapy was significantly related with tumor mutations ( 43 , 44 ). Thus, we analyzed the mutation profiles and found that the TMB between C1 and C2 was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the POLE gene confers to Polε both replicative and 3 to 5 repair capabilities for the new strand. Previous studies have suggested that different Polε gene members are associated with different stages of several different cancers, for example, Ma et al [13] pointed out in their study that mutations in POLE are associated with the development of various tumors; Zhu et al [14] found that people with POLE mutations are more prone to gastrointestinal tumors. However, the study of Raffone A et al [15]pointed out that patients with POLE mutations have increased numbers of tumor-in ltrating lymphocytes in endometrial cancer, suggesting a better prognosis, this seems to contradict the previous studies to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies have shown that four Polε genes are associated with the prognosis of gastrointestinal tumors [11], endometrioid carcinoma [12], lung cancer, and bladder cancer [13]. However, its role in hepatocellular carcinoma still lacks relevant studies and exploration.…”
Section: Introductionmentioning
confidence: 99%